2020
DOI: 10.31398/tpjf/27.2.2020a0006
|View full text |Cite
|
Sign up to set email alerts
|

Status of Water Quality in Fishponds Surrounding Manila Bay

Abstract: Fishponds around Manila Bay contributed an average of 41.19% of the total aquaculture production in the country. However, massive productions entail the intensification of ponds, which resulted in water quality deterioration. In 2016, Opinion et al. reported water quality in the aquaculture farms around the bay but does not include the other significant parameters required to be monitored, as stated in the DENR AO (2016). Thus, this study investigated the status of water quality in different pond systems surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, the current status of Manila Bay revealed that the levels of PO4 -3 (1.02 mg/L -2.42 mg/L) and NH3-N (0.90 mg/L -2.35 mg/L) were unsuitable for fish culture, although other important parameters like temperature, dissolved oxygen, pH, etc. were within the safe levels (Baldoza et al, 2020). Moreover, high water temperature (>32 °C) was the major challenge that has a significant impact on tilapia aquaculture, particularly in Luzon and Mindanao (Guerrero, 2019).…”
Section: Challenges In the Philippine Aquaculturementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the current status of Manila Bay revealed that the levels of PO4 -3 (1.02 mg/L -2.42 mg/L) and NH3-N (0.90 mg/L -2.35 mg/L) were unsuitable for fish culture, although other important parameters like temperature, dissolved oxygen, pH, etc. were within the safe levels (Baldoza et al, 2020). Moreover, high water temperature (>32 °C) was the major challenge that has a significant impact on tilapia aquaculture, particularly in Luzon and Mindanao (Guerrero, 2019).…”
Section: Challenges In the Philippine Aquaculturementioning
confidence: 99%
“…To monitor and maintain water quality, there should be a regular assessment or future researches of water quality, especially in aquaculture sites nationwide. In order to attain water quality standards, strict compliance with the Code of Good Aquaculture Practices must be imposed (Baldoza et al, 2020).…”
Section: Response To the Challenges And Recommendationmentioning
confidence: 99%
“…Water quality degradation issue in ecosystems that support aquaculture has remained one of the main problems for the sector as it triggers and causes an increase in the concentration of phosphates and nitrates, which could lead to deleterious effects because studies found that when the concentration of these materials are beyond the recommended level can cause adverse effects on dissolved oxygen concentrations of the site, trophic state and ultimately the well-being of the fauna and flora of the site (UN Water, 2015). For example, Manila Bay was found to be unsuitable for fish culture, although its temperature, DO level, and pH were within the safe levels, because its Phosphate and nitrate contents are too high (1.02 mg/L -2.42 mg/L, and 0.90 mg/L -2.35 mg/L) (Baldoza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%